A new broadband circularly polarized antenna with a single‐layer metasurface. Issue 7 (6th April 2020) - Liu, Yuan; Huang, Yu‐Xuan; Liu, Zhan‐Wei; Cai, Shu‐Ting; Xiong, Xiao‐Ming; Guo, Jing
Abstract: In this article, a new low‐profile broadband circularly polarized antenna with a single‐layer metasurface is designed. The metasurface is composed of 4 × 4 rotated rectangle‐loops. Compared to single rotated rectangle, introducing inner‐cut rectangle slot can increase the design flexibilities by changing this slot size for wider circularly polarized operating bandwidth and reduce the size of the antenna in same frequency. The proposed antenna has the advantages of a wide 3‐dB axial ratio bandwidth from 5.4 to 6.05 GHz and an excellent 10‐dB impedance bandwidth from 5 to 6.05 GHz.